Atomic-scale investigation of cation doping and defect clustering in the anti-perovskite Na3OCl sodium-ion conductor. Issue 5 (5th November 2021) - Goldmann, Benedek A.; Clarke, Matt J.; Dawson, James A.; Islam, M. Saiful
Abstract : We reveal the effects of cation doping and dopant-vacancy clustering on Na-ion conductivity in the anti-perovskite Na3 OCl solid electrolyte through atomistic simulations. Abstract : Solid-state batteries present potential advantages over their liquid-based electrolyte equivalents, including enhanced safety and increased energy density. In the search for novel solid electrolytes, the anti-perovskite family of materials are attracting growing interest. However, while there is significant work on Li-rich anti-perovskites, their Na-based counterparts and the atomistic effects of aliovalent doping on these materials are not fully characterised. Here, we investigate the effects on Na-ion conductivity of doping with divalent (Mg, Ca, Sr and Ba) and trivalent cations (Al and Ga), and of possible dopant-vacancy clustering in the anti-perovskite Na3 OCl by employing atomistic simulation techniques. Our results highlight the potential of Mg 2+, Ca 2+, Al 3+ and Ga 3+ doping due to their favourable incorporation and increased Na-ion vacancy concentration. Local defect clustering and binding energies are analysed, and such effects inhibit Na-ion conductivity in the doped Na3 OCl solid electrolyte at operating temperatures. These results provide a framework to guide future work on anti-perovskites to enhance their solid electrolyte properties.